2007
DOI: 10.3354/meps342205
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and distribution of nocturnal fishes over a coral reef during the night

Abstract: Coral reefs are characterized by high abundance of fishes, which often have marked effects on the recruitment, nutrition, and reproduction of coral reef inhabitants. Despite the fact that fish are active over the coral reef at night, very little is known of their whereabouts or about their contribution to those processes. In the present study, the abundance and distribution of nocturnal fishes were studied over a coral reef near Eilat, Red Sea. Sampling was conducted between the surface and 15 m depth, using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Planktivorous fish are a major component of coral reef communities both day and night (Hobson 1991;Holzman et al 2007). Most diurnal planktivores, including pomacentrids and planktivorous triggerfish (Balistidae) feed primarily on copepods (reviewed by Hobson 1991) which we found to be highly concentrated near the surface.…”
Section: Ecological Implicationsmentioning
confidence: 99%
“…Planktivorous fish are a major component of coral reef communities both day and night (Hobson 1991;Holzman et al 2007). Most diurnal planktivores, including pomacentrids and planktivorous triggerfish (Balistidae) feed primarily on copepods (reviewed by Hobson 1991) which we found to be highly concentrated near the surface.…”
Section: Ecological Implicationsmentioning
confidence: 99%
“…Diminished illumination at the end of the day triggers diurnal fishes to hide and nocturnal fishes to leave their daytime shelters (Jennings et al , 1999; Holzman et al , 2007). Light reflected by the moon may actually hamper these triggers.…”
Section: P‐values From Tukey's Hsd Post Hoc Test Comparing Percentagementioning
confidence: 99%
“…In many cases, however, such data are still not enough. Holzman et al (2007) showed the importance of nocturnal zooplanktivorous fish that connect lower-order and higher-order consumers. In addition, they indicated that the biomass of the nocturnal fishes is almost the same as that of diurnal fishes.…”
Section: Introductionmentioning
confidence: 99%